NUMERICAL SIMULATION OF 3-D SOBOLEV EQUATION VIA LOCAL MESHLESS METHOD - Ahmad, Imtiaz; Ahsan, Muhammad; Elamin, Abd Elmotaleb A. M. A.; Abdel-Khalek, Sayed; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
In this study, we use an effective meshless method to estimate the numerical solution of 3-D time-fractional Sobolev equation. The recommended meshless method is used for the spatial derivatives while the Liouville-Caputo derivative technique is utilized for the time derivative portion of the model equation. Accuracy of the method is assessed via error norms and comparison is made with the exact solution and other numerical methods given in more current literature, which demonstrated that the suggested strategy produces excellent performance and is more computationally efficient.
Keywords: local meshless method; Liouville-Caputo derivative; 3-D Sobolev equations; irregular domain